The electrical properties of BCZT lead-free ceramics induced by BaZrO3 seeds - Parjansri P. (2017)
© 2016 Trans Tech Publications, Switzerland. Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 (BCZT) ceramics were produced by using the seed-induced method. The nano-particle BZ (BaZrO 3 ) seeds were mixed with BaCO 3 , CaCO 3 , ZrO 2 and TiO 2 powder for preparing by the mixed oxide method. The XRD results indicated that all powder and sintered ceramic samples showed a pure perovskite phase with coexistence between rhombohedral and tetragonal phase. As the BZ seed content increased, the density of ceramics tended to decrease from 5.61 g/cm 3 to 5.37 g/cm 3 . The average grain size of the ceramics was in the range of 12.15-13.50 μm. The dielectric loss (tanδ) was less than 0.03 for all samples at room temperature (at 1 kHz). Other electrical properties, including dielectric constant (ϵ r ), remnant polarization (P r ), and piezoelectric charge coefficient (d 33 ) values decreased with increasing BZ seed doping with relates to the decreasing grain size and density of BCZT ceramics. However, the values of coercive field (E c ) decreased and piezoelectric voltage coefficient (g 33 ) increased with BZ seed doping.